OPTIMAL CONTROL OF NEUTRAL LIPIDS IN MICROALGAE PRODUCTION WITH NUTRIENT LIMITATION - ., Mardlijah; Riyantoko, Prismahardi Aji; Sanjaya, Suharmadi; Hanafi, Lukman (MATTER: International Journal of Science and Technology, 2018)
Consumer demand for fuel was increasing, while the supply of fuel has began dwindling. Therefore, it is necessary to undertake an effort to develop a renewable alternative energy such as usage of microalgae. Microalgae have four main components of substance i.e carbohydrates, proteins, nucleic acid and lipids. The relatively high lipid levels can be used as a source of biomass with using light, glucose, nutrients, carbon dioxide and water. Nutrient concentration is modified to keep the concentration of biomass through the dilution rate. In addition, carbon dioxide regulated also influence of microalage production in photobioreactor. Thereby, we used dilution rate and carbon dioxide mobilization as optimal control using Pontryagin Maximum Principle method to increased biomass and quota lipid production. Hence, the result is biomass increased as 4,5678% and quota lipid increased 44, 9727%.